ФОРМИРОВАНИЕ ПЛЕНОК ДИСИЛИЦИДА ТИТАНА В МОДИФИКАЦИИ С49 НА КРЕМНИИ, СТРУКТУРА, СВОЙСТВА - Асанов, Д.Ж.; Маркевич, М.И.; Камалов, А.Б. (SCIENCE and SOCIETY, 2023)
The most common methods for conducting solid-phase reactions for the formation of transition metal silicides are rapid heat treatment (RHT) using various energy sources. These methods are characterized by high productivity, manufacturability and reproducibility of results. The short process time minimizes the influence of the environment on the formation of silicides, and also minimizes the influence on the already formed elements of the active structure of the IMC. It has been established that with an increase in the treatment temperature of the heterosystem, the reflectivity of the modified surface increases. TRIKOTAJ MATOLARI NAQSHLARNI SHAKLLANTIRISH VA LOYIHALASHDA ZAMONAVIY TEXNIKA VA TEXNOLOGIYALARDAN FOYDALANISH A.Berdimbetova – katta o’qituvchi Ajiniyoz nomidagi Nukus davlat pedagogika instituti Tayanch soʻzlar: trikotaj, naqsh, bezak, mato, jakkard, press, futer, glad, lastik, ajur. Ключевые слова: вязание, узор, отделка, ткань, жаккард, пресс, футер, гладь, резинка, ажур.
Keywords: rapid heat treatment (RHT); IR range; C49 modification; titanium silicide; phase transition